2020
DOI: 10.3389/fvets.2020.565324
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Paratuberculosis on Milk Production, Fertility, and Culling in Large Commercial Hungarian Dairy Herds

Abstract: Paratuberculosis (PTBC) is a chronic disease caused by Mycobacterium avium subsp. paratuberculosis (MAP), which is common in dairy herds worldwide, although the scale of its impact on herd productivity is unclear. The aim of our study was to determine the differences between MAP ELISA positive vs. negative cows in terms of milk production and quality, reproductive parameters, and culling. The data of five large dairy herds that participated in the voluntary PTBC testing program in Hungary were analyzed. Cows w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Diseases and conditions ranked in order of decreasing impact. Disease/condition Impact (% increase) Reference Lameness 12.47 a Hernandez et al (2005) Cystic ovary 11.26 b Laporte et al (1994) Neosporosis 7.21 Kamga-Waladjo et al (2010) Dystocia 6.96 Gaafar et al (2011) Paratuberculosis 5.79 c Ozsvari et al (2020) Metritis 4.74 d Fourichon et al (2000) Retained placenta 2.74 e Fourichon et al (2000) Subclinical ketosis 1.50 f Fourichon et al (2000) GIN disease 1.20 g Walsh et al (1995) Displaced abomasum 0.00 Fourichon et al (2000) Mastitis 0.00 Fourichon et al (2000) Milk fever 0.00 Fourichon et al (2000) Fasciolosis 0.00 Mezo et al (2011) ; Howell et al (2015) a Median time to conception was 50 days longer among lame cows in the study, which is equivalent to a 12.5% increase in calving interval assuming a mean equivalent to the UK value ( Table 1 ). b Study indicated that cows with cystic ovarian disease (COD) had a mean calving interval of 425 days whereas cows without COD had a mean calving interval of 382 days, equivalent to an 11.3% increase.…”
Section: Methodsmentioning
confidence: 99%
“…Diseases and conditions ranked in order of decreasing impact. Disease/condition Impact (% increase) Reference Lameness 12.47 a Hernandez et al (2005) Cystic ovary 11.26 b Laporte et al (1994) Neosporosis 7.21 Kamga-Waladjo et al (2010) Dystocia 6.96 Gaafar et al (2011) Paratuberculosis 5.79 c Ozsvari et al (2020) Metritis 4.74 d Fourichon et al (2000) Retained placenta 2.74 e Fourichon et al (2000) Subclinical ketosis 1.50 f Fourichon et al (2000) GIN disease 1.20 g Walsh et al (1995) Displaced abomasum 0.00 Fourichon et al (2000) Mastitis 0.00 Fourichon et al (2000) Milk fever 0.00 Fourichon et al (2000) Fasciolosis 0.00 Mezo et al (2011) ; Howell et al (2015) a Median time to conception was 50 days longer among lame cows in the study, which is equivalent to a 12.5% increase in calving interval assuming a mean equivalent to the UK value ( Table 1 ). b Study indicated that cows with cystic ovarian disease (COD) had a mean calving interval of 425 days whereas cows without COD had a mean calving interval of 382 days, equivalent to an 11.3% increase.…”
Section: Methodsmentioning
confidence: 99%
“…Esta patología lleva a una infección que desencadena un proceso inflamatorio crónico granulomatoso a nivel intestinal en rumiantes domésticos y salvajes (Mallikarjunappa et al, 2020;McAloon et al, 2019). Aunque es común en dichos rumiantes, tiene elevada prevalencia en los hatos lecheros, lo cual genera graves consecuencias económicas y efectos adversos sobre el bienestar animal (Espinosa et al, 2020;Ozsvari et al, 2020;Sanchez et al, 2020).…”
Section: Artículos Originalesunclassified
“…PTB produces important economic losses in dairy herds worldwide due to increase in mortality, decrease in milk production, weight loss, premature culling and reduced slaughter value (1)(2)(3)(4). PTB has also been related to reduced fertility rates (5,6) and increased susceptibility to other diseases, particularly mammary infections (7). The importance of this disease would be even greater when considering its zoonotic potential and the risk of transmission of viable Map through pasteurized milk and milk products (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%